2020
DOI: 10.1007/s00425-020-03508-w
|View full text |Cite
|
Sign up to set email alerts
|

Benzopyrene induces oxidative stress and increases expression and activities of antioxidant enzymes, and CYP450 and GST metabolizing enzymes in Ulva lactuca (Chlorophyta)

Abstract: Main conclusionBenzopyrene is rapidly incorporated and metabolized, and induces oxidative stress and activation of antioxidant enzymes, and CYP450 and GST metabolizing enzymes in Ulva lactuca.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…B[ a ]P also decreases the level of reduced glutathione (GSH), vitamin C, and vitamin E, as well as increases the level of lipid peroxidation and protein carbonyl formation, as well as increases the expression of CYP1A1 and proinflammatory cytokines. Metabolites of B[ a ]P (mainly BPDE) and ROS created during transformation of B[ a ]P are the most important contributors to the oxidative effects provoked by this substance [ 102 , 103 , 104 , 105 , 106 ] ( Figure 5 ).…”
Section: Metabolism Of B[ a ]Pmentioning
confidence: 99%
See 1 more Smart Citation
“…B[ a ]P also decreases the level of reduced glutathione (GSH), vitamin C, and vitamin E, as well as increases the level of lipid peroxidation and protein carbonyl formation, as well as increases the expression of CYP1A1 and proinflammatory cytokines. Metabolites of B[ a ]P (mainly BPDE) and ROS created during transformation of B[ a ]P are the most important contributors to the oxidative effects provoked by this substance [ 102 , 103 , 104 , 105 , 106 ] ( Figure 5 ).…”
Section: Metabolism Of B[ a ]Pmentioning
confidence: 99%
“…Moreover, B[ a ]P has been reported to increase gene expression associated with inflammation and oxidative stress, as well as to deplete the expression and the activities of antioxidative enzymes, i.e., CAT, GPx, SOD, GST, and GR. Furthermore, B[ a ]P depleted nonenzymatic antioxidants levels, including GSH, Vit C, and Vit E. Metabolites of B[ a ]P (mainly BPDE) have been shown to induce ROS formation, as well as cause lipid peroxidation and protein carbonylation ( Figure 6 ) [ 102 , 103 , 104 , 105 ].…”
Section: Metabolism Of B[ a ]Pmentioning
confidence: 99%
“…González et al [33] showed that BaP was rapidly incorporated and metabolized in green algae Ulva lactuca, and induced oxidative stress and activation of antioxidant enzymes, as well as CYP450 and GST metabolizing enzymes in tested organism. BaP induced oxidative stress by changes in levels of hydrogen peroxide, superoxide anions, and lipoperoxides, as well as changes in activities of antioxidant enzymes: SOD, CAT, AP, GR, and GPx.…”
Section: The Effect Of Bap On Oxidative Stress In Vitro and In Vivomentioning
confidence: 99%
“…Numerous studies have indicated oxidative changes caused by BaP both in vitro [30,[34][35][36] and in vivo [31][32][33]37] (Table 1). Release of IL-1β and TNF-α from these cells [30] 1; 5 µM A549 and MCF-7 cancer cells Formation of ROS by influencing ROS/HIF-1α/HO-1 signaling pathway [34] 5 µM Human lung epithelial cells (BEAS-2B) ROS production and DNA damage [35] 100 nM; 1 µM Human monocytes and U937 cells ROS production, increase in the expression of CYP1A1 gene, and induction of NF-κB pathway [36] 250 mg kg -1 Mice-maternal exposure to BaP Increased expression of CYP1A1, SOD1, and SOD2 gene, and repressed GPX1 gene [37] 10; 20 µM Zebrafish embryos Decrease of CAT and SOD1 gene expression, increase H 2 O 2 and MDA level [31] 0.2 mg L −1 Adult zebrafish…”
Section: The Effect Of Bap On Oxidative Stress In Vitro and In Vivomentioning
confidence: 99%
“…The oxidative stress triggered by BaP induced the increase of ROS production in vitro [15]. As shown in Figure 2D, compared to the control group, BaP-exposure increased the intracellular ROS level by 970.7% (p < 0.01), which indicated that BaP-exposure caused fatal oxidative stress in Caco-2 cells.…”
Section: Effect Of Cpd-2 On Bap-induced Oxidative Stress and In Ammation In Caco-2 Cellsmentioning
confidence: 82%